Fiscal Policy and the Real Exchange Rate - Chatterjee, Santanu (IMF Working Papers; Working Paper ;, 2012)
Government spending on infrastructure has recently increased sharply in many emerging-market economies. This paper examines the mechanism through which public infrastructure spending affects the dynamics of the real exchange rate. Using a two-sector dependent open economy model with intersectoral adjustment costs, we show that government spending generates a non-monotonic U-shaped adjustment path for the real exchange rate with sharp intertemporal trade-offs. The effect of government spending on the real exchange rate depends critically on (i) the composition of public spending, (ii) the underlying financing policy, (iii) the intensity of private capital in production, and (iv) the relative productivity of public infrastructure. In deriving these results, the model also identifies conditions under which the predictions of the neoclassical open economy model can be reconciled with empirical regularities, namely the intertemporal relationship between government spending, private consumption, and the real exchange rate.